Urban regeneration economics: The case of Lisbon’s old downtown - Ribeiro, Francisco Loforte (International Journal of Strategic Property Management, 2010)
Buildings are one of the biggest assets of Lisbon’s central downtown accumulated over a period of several centuries. The efficient use and optimization of the value of these assets are a challenge for both the owners of individual buildings and for society as a whole. Recently, a new regeneration initiative was announced for old urban Lisbon’s downtown, covering three fields of intervention: the economic, social and physical fields. This paper presents a case study of the regeneration program for the Lisbon’s old downtown including an analysis of the framework used to assess the costs and benefits. First published online: 18 Oct 2010